حكم الطلاق المعلق على النكاح: دراسة فقهية مقارنة - يونس، عبدالمحسن طه (جامعة كركوك, 2021)
يتناول هذا البحث مسألة مهمة تتعلق بفقه الأسرة في باب الطلاق إذا علق على النكاح، وذلك إذا قال الرجل لامرأة: إن تزوجتك فأنت طالق، أو أن يقول: إن تزوجت امرأة فهي طالق، أو كل امرأة تزوجتها فهي طالق. والذي دفعني إلى الكتابة فيه حسب علمي المتواضع أني لم أجد بحثاً مستقلاً يجمع أحكامه، وينظم شتات مسائله. وسلكت فيه المنهج العلمي الرصدين والموضوعية، وتحري الإنصاف. وذلك بتحرير مذاهب الأئمة من كتبهم، وذكر أدلتهم، مع ترقيم الآيات القرآنية، وتخريج الأحاديث والآثار، وجمع المسائل من مصادرها الأصلية، وذكر خاتمة البحث وفيها أهم النتائج التي توصل إليها الباحث. وآخر دعوانا أن الحمد لله رب العالمين، وصلى الله وسلم على سيدنا محمد وآلة وصحبه.
The research deals with an important issue related to personal status in the matter of divorce, which is the divorce that is attached to marriage, if a man says to a woman: If you marry you then you are divorced, or he says: If you marry a woman then she is divorced, or every woman you marry is divorced. What motivated me to write about it is, according to my humble knowledge, that I have not found an independent research that collects its rulings, and helps science students to get acquainted with it, even to a small extent. It followed the scientific method sober and objectivity, and the investigation of fairness. And by liberating the doctrines of the imams from their books, and mentioning their evidence, with the numbering of the Qur’anic verses, the graduation of hadiths and monuments, and collecting issues from their original sources, and mentioning the conclusion of the research and the most important results that the researcher reached. And our final prayer is that praise be to God, Lord of the worlds, and may God’s prayers and peace be upon our Master Muhammad, his family and companions.
Keywords: الفقه الإسلامي -- التشريع الإسلامي -- الأحكام الشرعية -- الأحكام الفقهية -- حكم الطلاق المعلق على النكاح